Emergency nurses' attitudes towards the concept of witnessed resuscitation - Ana Laura García-Martínez; Cristóbal Meseguer-Liza (Universidade de São Paulo, 2018)
ABSTRACT Objective: to review the most relevant evidence on the nurses' attitudes towards witnessed resuscitation, in the inpatient and out-of-hospital spheres. Method: integrative literature review, covering the period from 2008 till 2015, using the databases PubMed, Lilacs and SciELO; in Spanish, English and Portuguese. The pediatric context was excluded from the study. Results: the synthesis of the data resulted in the inclusion of 10 articles, categorized as: positive attitudes and negative attitudes. Conclusions: discrepancies exist among the nurses from different contexts and geographical regions towards the concept; protocols need to be established for this situation, in view of the advantages evidenced in the literature, for the nursing professionals as well as the relatives. Witnessed resuscitation can represent an opportunity to understand and cope with the rational and irrational in the situation in a shared manner, as well as mitigate or dignify the mourning.